A proposed model for developing sports training planning parameters for team sports - ali, khaled; alborai, ahmed (sports creativity, 2025)
Although training is a cornerstone of human development, to which organizations and institutions dedicate considerable effort, time, and money to achieve high levels of athletic performance, this cannot be achieved without planning based on sound processes and scientific principles. Without such planning, progress or development in sports becomes a haphazard process, resulting in the waste of money, human resources, and time without achieving the set goals. The determinants of sports training planning, such as setting goals, selecting and organizing expertise, testing methods and tools, developing programs and schedules, managing time, evaluating results, and monitoring, have not been adequately addressed in research. This lack of research aims to establish a framework for sports training planning that coaches can use as a guide. Therefore, this research will study the determinants of sports training planning for team sports by identifying these determinants and proposing a model for them. Accordingly, this research aims to: 1- Develop a model for the determinants of sports training planning for team sports. The researcher used the survey research method and selected a research sample consisting of (23) experts and (233) coaches of team sports. In light of the results, the researcher developed a proposed model for the determinants of sports training planning for team sports coaches.